Breaking the cycle: Targeting of NDRG1 to inhibit bi-directional oncogenic cross-talk between pancreatic cancer and stroma - Geleta, Bekesho; Park, Kyung Chan; Jansson, Patric J; Sahni, Sumit; Maleki, Sanaz; Xu, Zhihong; Murakami, Takashi; Pajic, Marina; Apte, Minoti V; Richardson, Des R; Kovacevic, Zaklina (The FASEB journal, 2021)
Pancreatic cancer (PaCa) is characterized by dense stroma that hinders treatment efficacy, with pancreatic stellate cells (PSCs) being a major contributor to this stromal barrier and PaCa progression. Activated PSCs release hepatocyte growth factor (HGF) and insulin-like growth factor (IGF-1) that induce PaCa proliferation, metastasis and resistance to chemotherapy. We demonstrate for the first time that the metastasis suppressor, N-myc downstream regulated gene 1 (NDRG1), is a potent inhibitor of the PaCa-PSC cross-talk, leading to inhibition of HGF and IGF-1 signaling. NDRG1 also potently reduced the key driver of PaCa metastasis, namely GLI1, leading to reduced PSC-mediated cell migration. The novel clinically trialed anticancer agent, di-2-pyridylketone 4-cyclohexyl-4-methyl-3-thiosemicarbazone (DpC), which upregulates NDRG1, potently de-sensitized PaCa cells to ligands secreted by activated PSCs. DpC and NDRG1 also inhibited the PaCa-mediated activation of PSCs via inhibition of sonic hedgehog (SHH) signaling. In vivo, DpC markedly reduced PaCa tumor growth and metastasis more avidly than the standard chemotherapy for this disease, gemcitabine. Uniquely, DpC was selectively cytotoxic against PaCa cells, while "re-programming" PSCs to an inactive state, decreasing collagen deposition and desmoplasia. Thus, targeting NDRG1 can effectively break the oncogenic cycle of PaCa-PSC bi-directional cross-talk to overcome PaCa desmoplasia and improve therapeutic outcomes.